2018
DOI: 10.1101/284984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depleting Trim28 in adult mice is well tolerated and reduces levels of α-synuclein and tau

Abstract: 15Alzheimer's and Parkinson's disease are late onset neurodegenerative diseases that will require 16 therapy over decades to mitigate the effects of disease-driving proteins such tau and α-synuclein 17 (α-Syn). We recently found that TRIM28 regulates the levels and toxicity of α-Syn and tau 18 (Rousseaux et al., 2016), however, how TRIM28 regulates α-Syn and whether its chronic 19 inhibition later in life is safe remained unknown. Here, we show that TRIM28 mediates the 20 SUMOylation of α-Syn and tau, and that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…For shRNA‐mediated CHAF1A knockdown, shRNA targeting luciferase (shluc: 5′‐ACCGCCTGAAGTCTCTGATTAA‐3′) was used as negative control (Rousseaux et al, 2018). The shRNA target sequence against CHAF1A mRNA was: 5′‐CCGACTCAATTCCTGTGTAAA‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…For shRNA‐mediated CHAF1A knockdown, shRNA targeting luciferase (shluc: 5′‐ACCGCCTGAAGTCTCTGATTAA‐3′) was used as negative control (Rousseaux et al, 2018). The shRNA target sequence against CHAF1A mRNA was: 5′‐CCGACTCAATTCCTGTGTAAA‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…α‐Synuclein‐containing aggregates known as Lewy Bodies are a hallmark of PD, and, so far, 6 mutations in α‐synuclein have been associated with familial PD (Dehay & Fernagut, 2016). α‐Synuclein was first identified as a SUMO substrate by Dorval and Fraser (Dorval & Fraser, 2006), and subsequent work demonstrated that 11 of the 15 lysines in α‐synuclein can be SUMOylated (Kim et al., 2011; Krumova et al, 2011; Oh, Kim, Mouradian, & Chung, 2011; Rousseaux, de Haro, & Lasagna‐Reeves, 2016; Rousseaux et al, 2018). SUMOylation has been variously proposed to regulate α‐synuclein localization, turnover, aggregation and toxicity (Kim et al., 2011; Krumova et al., 2011; Oh et al., 2011; Rousseaux et al, 2016, 2018), suggesting that many aspects of α‐synuclein behaviour are under the control of SUMOylation, potentially depending on the specific lysines modified, the cellular context, and experimental system used.…”
Section: Sumoylation Of Other Proteins Involved In the Regulation Of mentioning
confidence: 99%
“…In addition to Twist1 and NR2F2 , other genes known to be essential for embryo survival and development but non-essential for adult survival also include Cripto-1 , Noda1 , Ror1 , Birc5 , Tbx2 , and Trim28 ( Rowley et al., 2004 ; Fukuda and Pelus, 2006 ; Strizzi et al., 2008 ; Abrahams et al., 2010 ; Rangel et al., 2012 ; Shabani et al., 2015 ; Kalyan et al., 2017 ; Rousseaux et al., 2018 ; Table 1 ). Up to date, only a small number of genes essential for embryo survival and development are examined in adult mice using inducible KO approach.…”
Section: Genes Essential For Embryogenesis May Be Non-essential For Smentioning
confidence: 99%